2012
DOI: 10.1104/pp.111.192682
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Deposition of Cell Wall Polysaccharides and Transcript Abundance of Related Cell Wall Synthesis Genes during Differentiation in Barley Endosperm

Abstract: Immunolabeling, combined with chemical analyses and transcript profiling, have provided a comprehensive temporal and spatial picture of the deposition and modification of cell wall polysaccharides during barley (Hordeum vulgare) grain development, from endosperm cellularization at 3 d after pollination (DAP) through differentiation to the mature grain at 38 DAP. (1→3)-β-d-Glucan appears transiently during cellularization but reappears in patches in the subaleurone cell walls around 20 DAP. (1→3, 1→4)-β-Glucan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 66 publications
(117 reference statements)
4
65
2
Order By: Relevance
“…S5, A, B, C, D, E, and F9), LAM (Supplemental Table S9), and RNAseq (see Fig. 4; Burton et al, 2008;Sreenivasulu et al, 2008;Mayer et al, 2012;Wilson et al, 2012;Thiel et al, 2012). The comparisons showed that it was indeed possible to produce consistent transcript profiles with different methods and to accurately reproduce the conditions of grain development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…S5, A, B, C, D, E, and F9), LAM (Supplemental Table S9), and RNAseq (see Fig. 4; Burton et al, 2008;Sreenivasulu et al, 2008;Mayer et al, 2012;Wilson et al, 2012;Thiel et al, 2012). The comparisons showed that it was indeed possible to produce consistent transcript profiles with different methods and to accurately reproduce the conditions of grain development.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria could be met through comparisons of the progress observed here for barley grain development with previously published studies in which identical conditions were used (Wilson et al, 2006(Wilson et al, , 2012. Moreover, it was possible to compare transcript profiles generated in this work by 44 K custom microarray analyses with data generated by quantitative RT-PCR, 22 K microarrays (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellulose, the most common biopolymer on Earth (Klemm et al 2005;Wilson et al 2012;Brinchi et al 2013), is composed of β-(14)-D-glucopyranose units (Meshitsuka and Isogai 1995) linearly arranged into elementary fibrils with lateral dimensions of 3 to 5 nm (Meier 1962;Ohad and Danon 1964;Heyn 1969;Blackwell and Kolpak 1975) and lengths of a few microns (Klemm et al 2005(Klemm et al , 2011Siró and Plackett 2010). These fibrils have segments with lower crystallinity and higher reactivity (Blackwell and Kolpak 1975;Henriksson et al 2007b;Pääkkö et al 2007).…”
Section: Introductionmentioning
confidence: 99%